2001
DOI: 10.1152/ajpgi.2001.281.2.g586
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of heme oxygenase-1 on trinitrobenzene sulfonic acid-induced colitis in rats

Abstract: Preliminary studies showed that the inducible form of heme oxygenase (HO-1) was induced and played a protective role in the process of inflammation. The present study investigated the possible role of HO-1 in 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis in rats. We measured HO-1 activity in TNBS-induced colitis in rats and analyzed the severity of colitis along with altered HO activity by assessing lesion area and myeloperoxidase activity. HO-1 mRNA and protein expressions were determined at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
97
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 49 publications
6
97
0
1
Order By: Relevance
“…Excess generation of ROS caused by the gut microenvironment breaks intestinal antioxidant systems in mice with DSS-induced colitis, thereby contributing to intestinal oxidative injury and initiating pro-inflammatory signaling (Tanaka et al 2007). In addition, several studies have demonstrated that inhibition of an antioxidant enzyme, heme oxygenase-1 (HO-1), leads to aggravation of DSSinduced colitis (Paul et al 2005;Wang et al 2001).…”
mentioning
confidence: 99%
“…Excess generation of ROS caused by the gut microenvironment breaks intestinal antioxidant systems in mice with DSS-induced colitis, thereby contributing to intestinal oxidative injury and initiating pro-inflammatory signaling (Tanaka et al 2007). In addition, several studies have demonstrated that inhibition of an antioxidant enzyme, heme oxygenase-1 (HO-1), leads to aggravation of DSSinduced colitis (Paul et al 2005;Wang et al 2001).…”
mentioning
confidence: 99%
“…HO-1, also known as heat shock protein 32, is a rate-limiting enzyme in the degradation of heme into biliverdin, carbon monoxide, and iron (50,51) and can attenuate tissue injury caused by various inflammatory stimuli (33)(34)(35)(52)(53)(54)(55)(56). We observed that an HO-1 inhibitor, SnPP, aggravated toxin A-induced enteritis, as evidenced by an increased fluid accumulation in WT mice.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have shown that HO-1 induction plays an important role in a number of cytoprotection responses, including anti-oxidative and anti-apoptotic effects (Motterlini et al, 2000) and a growing body of evidence has indicated that HO-1 induction acts an adaptive defense mech-www.biomolther.org anism to protect cells from various pathophysiological conditions (Maines, 1997). In addition, recent studies have also revealed that HO-1 induction modulates inflammatory process via suppressing the production of pro-inflammatory mediators, such as COX-2, TNF-α and iNOS (Wang et al, 2001). Furthermore, deficiency of HO-1 in mice exhibited a severe inflammation (True et al, 2007), while HO-1 over-expression prevented inflammatory responses in various experimental conditions (Otterbein et al, 2003;Onyiah et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…, 1997). In addition, recent studies have also revealed that HO-1 induction modulates inflammatory process via suppressing the production of pro-inflammatory mediators, such as COX-2, TNF-α and iNOS (Wang et al, 2001). Furthermore, deficiency of HO-1 in mice exhibited a severe inflammation (True et al, 2007), while HO-1 over-expression prevented inflammatory responses in various experimental conditions (Otterbein et al, 2003;Onyiah et al, 2013).…”
mentioning
confidence: 99%